Dispositional mindful awareness and savoring positive experiences: A prospective test of cognitive reappraisal as a mediator. (1st September 2020) - Cheung, Rebecca Y.M.; Ng, Melody C.Y.
Abstract: Grounded in mindfulness-to-meaning theory and broaden-and-build theory, the present study tested the longitudinal relations between mindful awareness, cognitive reappraisal, and savoring positive experiences among Chinese emerging adults in Hong Kong. A total of 194 emerging adults at 18–27 years of age completed a set of questionnaires for three times, with a 3-month lag between time points. Findings based on structural equation modeling indicated that the association between mindful awareness and savoring positive experiences was mediated by cognitive reappraisal, over and above the effects of sex, age, and autoregressive control variables. These findings provided evidence for short-term longitudinal relations between these variables in the Chinese context. In order to foster the savoring of positive experiences, researchers and practitioners should be made aware of the possible chain of mechanisms associated with mindful awareness. Highlights: Cognitive reappraisal mediates between mindful awareness and savoring positive experiences longitudinally Mediating role of cognitive reappraisal applies to the Chinese context Cultivating mindful awareness serves important functions to foster positive psychological resources of well-being